An Economic Analysis on Factors Influencing the Family Income of Livestock Farmers: A North-Eastern Karnataka Study - Yasmeen; Patil, Suresh S.; Ram, Jagjiwan; Hiremath, G. M.; Koppalkar, B. G. (International Journal of Livestock Research, 2020)
Livestock is an integral part of farming in the agricultural scenario of the country as well as the state. Since ancient times, cattle and buffaloes are maintained to meet the daily requirements of milk, draught power, field operation and for valuable organic manure. Sheep, goats, poultry and pigs are used to extract the meat, which is the major source of animal protein in the country. Multiple regression function was fitted and regression coefficients of various factors influencing the total family income of livestock farmers were identified. Among different explanatory variables, per cent share of dairy income to total income (326.09), per cent area under irrigation (473.26) and number of milch animals (17027.92) were significantly influencing the total income of the livestock farmers. Whereas, total dairy expenditure was negatively significant. Livestock provides major source of income to the landless labourers, marginal and small farmers to sustain their family income in the area of study.